THE ROASTING COFFEE EQUIPMENT WITH AUTOMATIC TEMPERATURE CONTROL AND STEAM / HOT AIR DISPOSAL TO ACCELERATE COOLING PROCESS OF SUPPLY RESULTS IN VILLAGE FRUIT OF REGENCY KARO - Junedi Ginting; Aditia Warman; Juliati Br Tarigan (Talenta Publisher, 2018)
This devotional activity has been carried out and runs well in line with the aim of assisting thecommunity of coffee farmers in Buah Raya Village for the management of coffee beans mainly byway of roasting. The tool used is 1 set of coffee cutting equipment equipped with temperaturecontrol and exhaust vapor / hot air to accelerate the cooling process results from roasting. Testingthe production of the tool is done by inserting the coffee beans to be roasting and then setting thetemperature button on the equipment to the temperature used in accordance with the coffee beansare inserted, after finished activate the exhaust steam / hot air and then wait a while for the coffeebeans are cold. Then move the coffee beans to the aluminum plate box as a shelter.